The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2016
DOI: 10.21037/jss.2016.08.08
|View full text |Cite
|
Sign up to set email alerts
|

Single-level selective dorsal rhizotomy for spastic cerebral palsy

Abstract: The management of cerebral palsy (CP) is complex and requires a multidisciplinary approach. Selective dorsal rhizotomy (SDR) is a neurosurgical technique that aims to reduce spasticity in the lower limbs.A minimally invasive approach to SDR involves a single level laminectomy at the conus and utilises intraoperative electromyography (EMG). When combined with physiotherapy, SDR is effective in selected children and has minimal complications. This review discusses the epidemiology of CP and the management using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 44 publications
(66 reference statements)
1
13
0
Order By: Relevance
“…These results were comparable to those SDR managed via the traditional way. Not surprisingly, like what earlier studies concluded [ 1 , 14 , 15 , 17 – 19 ], our data showed as well that mild cases improved much better than those severe ones. Cases with their pre-op GMFCS level of II and III had more chance to have their level upgrade than those with IV and V (24/57 vs. 3/24) after the rehabilitation therapy.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…These results were comparable to those SDR managed via the traditional way. Not surprisingly, like what earlier studies concluded [ 1 , 14 , 15 , 17 – 19 ], our data showed as well that mild cases improved much better than those severe ones. Cases with their pre-op GMFCS level of II and III had more chance to have their level upgrade than those with IV and V (24/57 vs. 3/24) after the rehabilitation therapy.…”
Section: Discussionsupporting
confidence: 92%
“…To reduce muscle tone mainly in particular spastic muscles of lower limbs in spastic cerebral palsy (CP) children via single-level approach selective dorsal rhizotomy (SL-SDR) using a universally applicable rhizotomy protocol still remains challenging [ 1 ]. In the current study, we investigated whether our modified rhizotomy protocol-guided SL-SDR which could effectively decrease muscle tone of those particular spastic muscles in hemiplegic cases could be applied as well in spastic diplegic and quadriplegic pediatric CP cases.…”
Section: Introductionmentioning
confidence: 99%
“…Short- (18 months) and long-term (13 years) results at our institution based on these criteria have been published previously. 21 , 22 Our criteria here share similar items to those published by other institutions, such as Oswestry 23 and Great Ormond Street 24 ( Appendix A ). Exceptions include our use of 3DGA and standardized assessment tools of spasticity, such as the Ashworth scale 25 and the Hypertonia Assessment Tool (HAT).…”
Section: Patient Selection For Sdrmentioning
confidence: 99%
“…Extensive rehabilitation is required and is part of the SDR protocol in most institutions performing this procedure. 24 , 38 , 55 , 61 Physiatrists and physical therapists should be part of the team giving input into the patient selection process as well as communicating to parents regarding postoperative expectations and rehabilitation plans. At our institution, rehabilitation following SDR differs significantly to rehabilitation following SEMLS.…”
Section: Sdr Within a Multi-disciplinary Multi-modal Approachmentioning
confidence: 99%
“…The available treatments provide some relief; SDR provides spasticity reduction and provides modest improvement or maintenance of function [9]. The strength of the evidence supporting the treatments is weak however, guidelines for use exist [10], but no cost‐effectiveness studies have been conducted [11].…”
Section: Spasticity and Its Treatmentmentioning
confidence: 99%